2020
DOI: 10.1038/s42003-020-01509-9
|View full text |Cite
|
Sign up to set email alerts
|

DEFECTIVE ENDOSPERM-D1 (Dee-D1) is crucial for endosperm development in hexaploid wheat

Abstract: Hexaploid wheat (Triticum aestivum L.) is a natural allopolyploid and provides a usable model system to better understand the genetic mechanisms that underlie allopolyploid speciation through the hybrid genome doubling. Here we aimed to identify the contribution of chromosome 1D in the development and evolution of hexaploid wheat. We identified and mapped a novel DEFECTIVE ENDOSPERM–D1 (Dee-D1) locus on 1DL that is involved in the genetic control of endosperm development. The absence of Dee-D1 leads to non-via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A search for orthologous groups for the eight pathways of pigment biosynthesis and their precursors identified 307 KEGG orthologs involved in these processes (Table S3). A review of the literature [18,19,38] identified 155 Arabidopsis and 42 rice genes involved in the molecular processes of seed development (Table S3). Of these genes, 193 were found Leaves correspond to seed traits described in [1] ( for trait abbreviation, see Section 4.2.…”
Section: Gene Prioritizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A search for orthologous groups for the eight pathways of pigment biosynthesis and their precursors identified 307 KEGG orthologs involved in these processes (Table S3). A review of the literature [18,19,38] identified 155 Arabidopsis and 42 rice genes involved in the molecular processes of seed development (Table S3). Of these genes, 193 were found Leaves correspond to seed traits described in [1] ( for trait abbreviation, see Section 4.2.…”
Section: Gene Prioritizationmentioning
confidence: 99%
“…Studies have shown that seed size and shape in wheat are controlled by a large number of loci located on almost all chromosomes [6][7][8][9][10][11][12][13]. Identification of these loci combined with molecular analysis can identify genes that are involved in controlling seed weight or size [14][15][16][17][18][19]. Based on genetic and molecular studies in both the model organism Arabidopsis thaliana and cereals, it is now established that seed weight is affected by multiple molecular and genetic aspects that lead to dynamic changes in cell division, expansion, and differentiation during seed development.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we identified and mapped a novel DEFECTIVE ENDOSPERM–D1 ( Dee-D1 ) locus on chromosome arm 1DL that is involved in the genetic control of endosperm development 52 . The absence of Dee-D1 leads to non-viable grains in distant crosses and alters grain shape, which negatively affects GN and TGW.…”
Section: Discussionmentioning
confidence: 99%
“…These cells redifferentiate to become starchy endosperm cells and likely are the source of the so-called subaleurone cells found adjacent to the aleurone layer in the starchy endosperm in all cereals. Several collections of mutants such as dek (defective kernel) [22], and Dee-D1 (DEFECTIVE ENDOSPERM-D1) [23], physically located on the long arm of chromosome 1D involved in the genetic control of endosperm development in wheat. The absence of Dee-D1 in the genome of hexaploid wheat leads to a decrease in the number of grains and thousand grain weights.…”
Section: Starchy Endospermmentioning
confidence: 99%